Intelligent Tracking Algorithms in Collaborative Robotic Systems: Application of Camshift and Kalman Filter - Gurin, D. (My University, 2025)
In this paper, considers modern approaches to solving the problems of tracking objects in collaborative robotic systems using intelligent algorithms. Special attention is paid to the use of the CAMShift algorithm and the Kalman filter, which are actively used to track the dynamics of object movement in various environments. The principles of operation of both methods, their advantages and disadvantages, as well as the possibilities of integration into collaborative robotics systems are analyzed. The article also contains a comparative table that summarizes the key characteristics of the algorithms and contains reflections on the prospects for their use in real-time conditions.
Keywords: Industry 5.0; CAMShift; Kalman filter; cobot